Collins, Mark. Stateless. Ladywell, Thomastown, Co. Kilkenny: Pillar, 2006. 314. pp. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
This novel appeared in the Republic of Ireland in October 2006, one might perhaps say for the 50th anniversary of the 1956 Revolution in Hungary. Its title is Stateless, rhyming with the English translation of the title of Nobel-prize winner Imre Kertész’s novel, Fateless. It is the first novel of a young journalist, Mark Collins, whose mother is a Hungarian who left her home country for Ireland as a child in the aftermath of the defeated revolution. Stateless is based on family experiences as well as on documents to be found in Irish archives about how Ireland hosted 530 refugees from Hungary who escaped there at the end of 1956 and in early 1957. Although the book is marked by the flaws that often charactrise the first novel of a young author, the reading of Stateless should be a must for those who cherish overly romantic notions about Irish-Hungarian historical relations and national similarities without being aware of the full picture.